The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/milmed/usaa253
|View full text |Cite
|
Sign up to set email alerts
|

From the Dexterous Surgical Skill to the Battlefield—A Robotics Exploratory Study

Abstract: Introduction Short response time is critical for future military medical operations in austere settings or remote areas. Such effective patient care at the point of injury can greatly benefit from the integration of semi-autonomous robotic systems. To achieve autonomy, robots would require massive libraries of maneuvers collected with the goal of training machine learning algorithms. Although this is attainable in controlled settings, obtaining surgical data in austere settings can be difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[83]. A training data set for automated surgical operations by robots and methods for its propagation and sharing to other robotic platforms were discussed in [84] in order to develop the capability to perform emergency medical/surgical procedures using AI to tackle the highly emergent situations where availability of healthcare professionals risks lives. Those surgical maneuvers were compiled as a library for sharing for continuous learning and improvements.…”
Section: Cps Componentsmentioning
confidence: 99%
“…[83]. A training data set for automated surgical operations by robots and methods for its propagation and sharing to other robotic platforms were discussed in [84] in order to develop the capability to perform emergency medical/surgical procedures using AI to tackle the highly emergent situations where availability of healthcare professionals risks lives. Those surgical maneuvers were compiled as a library for sharing for continuous learning and improvements.…”
Section: Cps Componentsmentioning
confidence: 99%
“…It is important to know that every time a procedure is carried out with the da Vinci robotic system, the motion data of the robotic arms are being recorded and transmitted to the manufacturer. Engineers and computer scientists hope that the sheer quantity of these data will permit the generation of functioning algorithms that will ultimately result in more autonomous actions by surgical robots [71]. Although it is tempting to wonder whether or not this is possible, perhaps this is not the most important question.…”
Section: Robotic-assisted Surgery and Autonomous Actionsmentioning
confidence: 99%
“…In the no-transfer scenario, the training and testing data were obtained from the same domain, compared to a domain-transfer scenario where training data is a blend of simulated and real robot data but tested on real robot data only. Authors in [19] tested this on several types of robots and found that the transfer model showed an accuracy of 81%, 97.5%, and 93% for the YuMi, Taurus II, and the da Vinci robot, respectively. While, in the YuMi case, the ratio of real-to-simulated data was 22% to 78%, later were trained only with simulation data.…”
Section: B Partial Automationmentioning
confidence: 99%